2015
DOI: 10.18632/oncotarget.3812
|View full text |Cite
|
Sign up to set email alerts
|

A small molecule inhibitor of atypical protein kinase C signaling inhibits pancreatic cancer cell transformed growth and invasion

Abstract: Pancreatic cancer is highly resistant to current chemotherapies. Identification of the critical signaling pathways that mediate pancreatic cancer transformed growth is necessary for the development of more effective therapeutic treatments. Recently, we demonstrated that protein kinase C iota (PKCι) and zeta (PKCζ) promote pancreatic cancer transformed growth and invasion, by activating Rac1→ERK and STAT3 signaling pathways, respectively. However, a key question is whether PKCι and PKCζ play redundant (or non-r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
44
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(45 citation statements)
references
References 34 publications
1
44
0
Order By: Relevance
“…Our data establish a novel PKCι-AMOT-YAP1 signaling pathway that drives OSC tumorigenesis and is active in primary OSC tumors. Our finding that ANF, a compound that inhibits oncogenic PKCι signaling, 3, 4, 8, 25, 34 blocks PKCι-YAP1 signaling and inhibits OSC growth in vitro and OSC tumorigenesis in vivo suggests a plausible therapeutic intervention strategy for treatment of OSC. In this regard, we have observed preliminary clinical activity of ANF in ovarian cancer patients in a maintenance setting.…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…Our data establish a novel PKCι-AMOT-YAP1 signaling pathway that drives OSC tumorigenesis and is active in primary OSC tumors. Our finding that ANF, a compound that inhibits oncogenic PKCι signaling, 3, 4, 8, 25, 34 blocks PKCι-YAP1 signaling and inhibits OSC growth in vitro and OSC tumorigenesis in vivo suggests a plausible therapeutic intervention strategy for treatment of OSC. In this regard, we have observed preliminary clinical activity of ANF in ovarian cancer patients in a maintenance setting.…”
Section: Discussionmentioning
confidence: 82%
“…Treatment of OSC cells with auranofin (ANF), which inhibits PKCι signaling, 4, 25 induced loss of nuclear YAP1 (Fig. 9A).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…GSI inhibitors of NOTCH exhibit potent anti-tumor activity in glioma (Fan et al, 2010; Fan et al, 2006), lung (Konishi et al, 2007), and ovarian cancers (Groeneweg et al, 2014a; Groeneweg et al, 2014b) and the potent GSI PF-03084014 has shown clinical promise in advanced cancer patients (Messersmith et al, 2015). The anti-rheumatoid gold salts ATM and ANF selectively inhibit PKCι signaling and block growth of lung (Erdogan et al, 2006; Fields et al, 2007; Regala et al, 2008; Stallings-Mann et al, 2006), pancreatic (Butler et al, 2015; Scotti et al, 2012) and ovarian (Wang et al, 2013) tumors in vitro and in vivo , and two clinical studies have demonstrated proof-of-principle for PKCι inhibitor-based therapy with ATM (Mansfield et al, 2013) and ANF (Jatoi et al, 2014). Our finding that GSI and ANF exhibit highly synergistic anti-tumor activity suggests a novel therapeutic approach to treat KRAS LADC, a tumor sub-type for which there is a dire need for effective targeted therapeutics.…”
Section: Discussionmentioning
confidence: 99%
“…7 aPKC has been also evaluated successfully as a target for small molecule drug candidates against pancreatic cancer cells. 8 Here we present preliminary data on the synthesis and biological studies of 3a and 3b azido analogues of S18. Ceramide analogs with fluorescent tags proved to be useful for the study of dynamics and visualizing membrane architecture.…”
mentioning
confidence: 99%